Impact of Gamma Irradiation and Kale Leaf Powder on Amino Acid and Fatty Acid Profiles of Chicken Meat under Different Storage Intervals - Khalid, Waseem (2022)
he present study was planned to determine the effect of kale leaf powder and gamma rays on variations in the pH, amino acid and fatty acid profiles of chicken meat at different storage intervals. Significant changes (p ≤ 0.05) in the pH, amino acid and fatty acid profiles of chicken meat following different treatments (KLP (1% and 2%) and gamma irradiation (3k Gy)) were reported at 0, 7 and 14 days of storage. The pH value of the chicken meat sample decreased with the addition of kale leaf powder, whereas the value increased following a gamma irradiation dose of 3 kGy and with the passage of time. During different storage intervals, the minimum reduction in the amino acid and fatty acid quantities in the chicken meat samples was reported after gamma irradiation treatment. However, with the addition of KLP, the amount of amino acids and fatty acids in the chicken meat samples increased. Conclusively, the pH was observed to be reduced in the meat following combined treatment (irradiation + KLP), whereas the 2% KLP treatment improved the amino acid and fatty acid profiles of the chicken samples.